Can You Count on What You See? Numerosity Extraction and Its Association With Verbal Number Skills in Early Childhood. - Klein-van 't Noordende, Jaccoline E.; Moeller, Korbinian; van Hoogmoed, Anne H.; Kroesbergen, Evelyn H. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2025)
In young children in particular, processing numerical magnitudes is influenced by spatial characteristics of those magnitudes (e.g., extent). Gradually, children will learn to dissociate numerosity from spatial information and understand that objects represent discrete numerical quantities. In the present study, we investigated whether 5-year-old children extract numerosity disregarding spatial stimulus characteristics and in what way numerosity extraction is associated with verbal number skills (counting and initial addition). Five-year-old children were presented with a newly developed task to measure numerosity extraction on two timepoints, several months apart. Each item contained three rows of differently sized rectangles. Children had to identify which two rows contained the same number of rectangles. On congruent items, these two rows were similar in length. On incongruent items, the two rows equal in numerosity varied in length. Analyses indicated that some 5-year-old children showed numerosity extraction, but others had difficulties to disentangle numerosity from spatial characteristics. Numerosity extraction was predicted over time by initial addition but not counting skills, although there was a concurrent association between counting skills and numerosity extraction at timepoint 2. Numerosity extraction did not predict either initial addition or counting over time. These results suggest that the ability to disentangle numerosity from spatial characteristics is still developing around 5 years of age and that verbal number skills foster this development. Verbal number skills probably further refine nonsymbolic magnitude processing (in this study, numerosity extraction), while nonsymbolic magnitude processing does not underlie verbal number skills.